PENGARUH PENERAPAN MODEL PAIKEM TERHADAP MOTIVASI BELAJAR SISWA - Sintia, Ni Kadek; Rasmini, Ni Wayan; Rudiarta, I Wayan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Abstract Boring learning is one of the causes of low student motivation. PAIKEM as a learning model is a solution to overcome these problems. This study aims to find the influence between the application of the PAIKEM model on students' learning motivation in the subject of Hindu Religious Education and Ethics at SMPN 1 Mataram This research was conducted with an Associative Quantitative approach and Ex-Post Facto method. Research data were obtained through questionnaires, observations, and documentation. Data analysis assisted by SPSS 25.0 was carried out to conduct descriptive analysis and inferential analysis which included prerequisite tests, simple regression analysis, and hypothesis testing. The study population was all Hindu students at SMPN 1 Mataram totaling 381 people. The sample used was class VIII of 137 students. The results of data analysis: the mean (average) value for the application of the PAIKEM model is 84.01 with data distribution showing that 41 students (30.37%) stated very well, 81 students (60%) stated well, and 13 students (9.63%) stated quite well. While the results of the analysis of the mean value of student learning motivation are 82.89 with data distribution showing that there are 46 students (34.07%) stating very good, 62 students (45.93%) stating good, and 27 students (20%) stating quite good. Through simple regression analysis, it was found that variables X and Y had a relationship of 33%. Based on the results of the product moment correlation test, the pearson corelation value is 0.579 with the results of Df (degrees of freedom) = n-2 or 135-2 = 133. At the 0.05 significance level, the r table value is 0.169. This means that rcount = 0.579> rtable = 0.169. So it can be concluded that Ho is rejected and Ha is accepted. From the results of this study it can be recommended to teachers to apply PAIKEM in learning. Keywords: PAIKEM Model, Learning Motivation, Students